Obstetrical transfusion medicine knowledge among faculty and trainee obstetricians: a prospective knowledge assessment study. Issue 6 (26th September 2016) - Morris, S.; Yudin, M. H.; Callum, J.; Alam, A.; Herold, J.; Lin, Y.
ABSTRACT: Objectives: To evaluate the current state of transfusion medicine (TM) knowledge among obstetricians using a valid assessment tool. Background: Transfusion issues are common in obstetrical patients. Methods: Knowledge topics were identified and rated by experts in obstetrics, anaesthesia, haematology and TM using a modified Delphi method. A knowledge assessment tool was developed and validated during pilot testing. The assessment tool, consisting of 15 multiple choice questions, was administered electronically to members of the Society of Obstetricians and Gynaecologists of Canada (SOGC). Results: A total of 192 SOGC members completed the assessment tool: 121 faculty obstetricians and 71 trainees. The average score was 65·8% ± 15·5. Scores for faculty were higher than trainees (68·9% ± 13·5 vs 60·6% ± 17·2; P < 0·001). Respondents performed well on questions related to red blood cell (RBC) transfusion and anaemia management but had lower scores on questions related to non‐RBC transfusion and management of alloantibodies and fetomaternal haemorrhage (FMH) testing. There was no improvement in scores with increasing trainee level, years of practice, hours of formal TM training or experience with massive haemorrhage. Only self‐rated knowledge was associated with scores ['no knowledge' or 'beginner' 63·1% ± 15 vs 'intermediate' or 'advanced' 68·9% ± 13·3 ( P = 0·007)]. Of the respondents, 93·8% felt additional training in TM would be helpful. Conclusions: Overall knowledge assessment scores indicate the need for educational intervention, particularly with respect to non‐RBC blood product use, management of FMH and management of pregnancies complicated by alloantibodies. The study also demonstrated a desire for additional TM training.